2002
DOI: 10.1073/pnas.142305699
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cortical activation and perception investigated with invisible stimuli

Abstract: The aim of this work was to study the relationship between cortical activity and visual perception. To do so, we developed a psychophysical technique that is able to dissociate the visual percept from the visual stimulus and thus distinguish brain activity reflecting the perceptual state from that reflecting other stages of stimulus processing. We used dichoptic color fusion to make identical monocular stimuli of opposite color contrast ''disappear'' at the binocular level and thus become ''invisible'' as far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
164
1
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(189 citation statements)
references
References 29 publications
19
164
1
5
Order By: Relevance
“…This indicates the presence of a persistent neural representation of subjectively invisible stimuli. Consistent with this finding, several fMRI and EEG studies have shown that ventral visual cortex can retain a neural representation of subjectively (and objectively) invisible stimuli (25,26,(31)(32)(33). Our findings go beyond this earlier work by extending such observations to the new situation of low-level perceptual completion, further confirming that activation in visual cortex is not sufficient for conscious awareness.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This indicates the presence of a persistent neural representation of subjectively invisible stimuli. Consistent with this finding, several fMRI and EEG studies have shown that ventral visual cortex can retain a neural representation of subjectively (and objectively) invisible stimuli (25,26,(31)(32)(33). Our findings go beyond this earlier work by extending such observations to the new situation of low-level perceptual completion, further confirming that activation in visual cortex is not sufficient for conscious awareness.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with this, frequencytagged EEG and MEG studies also demonstrate reduced power for stimuli that become invisible during binocular rivalry (10, 24). Moreover, recent fMRI studies consistently find that signals from human ventral visual cortex are reduced when stimuli are invisible, compared with identical physical stimulation that results in conscious perception (25,26). Thus, a consistent general feature of the human visual system is of stronger neural activity associated with conscious perception of a stimulus compared with equivalent physical stimulation that remains unconscious (27).…”
Section: Discussionmentioning
confidence: 95%
“…However, a second, equally important conclusion can be drawn from the results described: the presence of different, directionally selective neuronal populations in human V5, as is the case with its monkey homologue (14). It is known from previous studies that nonperceived monocular information is not lost beyond the point of convergence of the two eyes in V1, but is still present in the higher visual areas of the brain (2,6,7,24). If human V5 also contains directionally selective units, the two monocular inputs in the Opposite condition should activate two different neuronal populations in this area (i.e., twice as many neurons as activated by the Same condition).…”
Section: Psychophysicsmentioning
confidence: 64%
“…In recent years, a diversity of putative objective correlates of consciousness have been described. Candidates include sustained activity in primary visual area V1 (1-3), amplification of perceptual processing (4,5), correlation across distant regions (6,7), joint parietal, frontal, and cingulate activation (4,8,9), cortico-cortical or thalamo-cortical ␥-band oscillations (10,11), and P300 waveform (12). Although these diverse measurements are often viewed as incompatible findings about the nature of conscious states, an increasingly attractive alternative is that they constitute different reflections of a single underlying phenomenon: the settling of brain activity into a temporary metastable state of global activity.…”
mentioning
confidence: 99%